Case study on the International Food Policy Research Institute (IFPRI) and conditional cash transfer (CCT) and non-conditional cash transfer (NCCT) programs - Behrman, Jere R.; Calderon, Maria Cecilia (International Food Policy Research Institute, 2009)
The objective of this study is to attempt to characterize the apparent influence and impact of IFPRI in relation to evaluation of conditional cash transfers (CCT) and non-conditional cash transfers (NCCT) programs, in both cases including both programs in which IFPRI was involved in the evaluations and programs in which IFPRI was not involved in the evaluations. This effort is a broader effort related to a previous study on the IFPRI influence on one particular influential CCT program, the Mexican PROGRESA / Oportunidades program, which concluded that IFPRI had substantial impact with a high benefit-to-cost ratio. The greater breadth in this study comes at the cost of less depth. The paper first discusses some preliminaries: (1) definitions of CCT and NCCT programs, and (2) the challenges in assessing the influence and impact of IFPRI on and through such programs. It then presents a tabulated database of CCT and NCCT programs that includes 17 characteristics for 41 CCT and 36 NCCT programs worldwide. Next, it presents the meta-description of IFPRI?s role in international learning about these programs based on (1) Google Scholar searches and (2) e-mail interviews with selected key informants for all of the CCT and NCCT programs included in the data base. Six groups of e-mails similar in spirit were written to: (1) key informants in CCT programs for which IFPRI was involved in the evaluation, (2) key informants in CCT programs for which IFPRI was not involved in the evaluation, (3) key informants for NCCT programs in which IFPRI was involved in evaluations, (4) key informants for NCCT programs in which IFPRI was not involved in evaluations, (5) key informants for the PROGRESA / Oportunidades CCT program who had provided responses for the Behrman (2007) study of that program, and (6) a small group of ?experts? on cash transfer programs. In some cases, the same informant was knowledgeable about more than one program; therefore we constructed informant-program data. A total of 627 key informant-program combinations were identified from which we obtained 497 (79.2 percent) valid email addresses. We received 369 (58.9 percent) original responses and we were able to conduct 220 (35.1 percent) interviews. The typical questions were structured as indicated below for a key informant who was involved with the CCT program in which IFPRI was involved in the evaluation.